Factors affecting the ability to apply ABC accounting method: Case study of Vietnamese consumer goods enterprises - NGUYEN, Tung Dao (The journal of contemporary issues in business and government, 2021)
The article analyzes the impact of factors affecting the ability to apply the ABC accounting method of Vietnam consumer goods enterprises, providing more empirical evidence on factors affecting the ability to apply ABC accounting method. The research method uses the survey of consumer goods enterprises. Quantitative research is done with SPSS 25 software. Research results show that 6 factors positively affect the ability to apply ABC accounting method, in which the level of human resources is the influencing factor. has the strongest influence on the ability to apply ABC accounting method of enterprises in the consumer goods industry. Based on the research results, the author has proposed recommendations to improve the ability to handle ABC accounting methods of enterprises in the consumer goods industry, thereby contributing to improving the performance of enterprises in the industry consumer goods.